Development Finance and Distributive Politics: Comparing Chinese and World Bank Finance in sub-Saharan Africa - Keyi Tang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2021)
When development finance becomes available to weak states, which parts of the state will receive the windfall gains? Development finance does not always reach the people who need it the most, both within and across countries. In this research, Keyi Tang examines how donors' preferences and recipient countries' regime types affect the subnational distribution of development finance. By combining a large-N analysis of Chinese and World Bank's loans and grants to 48 African countries between 2000-2012 and small-N case studies of a hybrid regime, Zambia, and an autocratic regime, Ethiopia, Keyi finds that domestic politics play a bigger role than donors' conditionality in development finance allocation. The more democratic a regime is, the more likely co-ethnic regions of the incumbent leader are to receive finance from both China and the World Bank. Democracy may not always help prevent clientelism but may actually facilitate it under weak institutions.
Keywords: 330